12 - The Petty Bourgeoisie in the Thought of Amilcar Cabral and Walter Rodney - Shivji, Issa G. (CODESRIA Bulletin, 2025)
Paper presented to the International Symposium entitled: ‘Amilcar Cabral: A national and universal heritage’, in commemoration of the centenary of Cabral’s birth held at Cabo Verde and Guinea-Bissau from 9 to 12 September, 2024 On Petty Bourgeoisie One of the most debated ideas of Amilcar Cabral is that of the suicide of the petty bourgeoisie. Much has been written on this idea, a few in con- text but much out of context, thinking of it as a dictum or an edict. In revisiting this statement, I want to locate it in its historical and political context: why it was said, in what context and with what political purpose in mind. Cabral and Walter Rodney always emphasised the speciﬁcity of discourse—to be concrete and contextual and dis- cuss concepts and ideas emanating from our own speciﬁc conditions and political practices. Before I do this, it is relevant to discuss the social category of petty bourgeoisie, which both Cabral and Rodney used freely in their writings. This is important because their meaning of ‘petty bourgeoisie’, particularly in the political context, is slightly diJerent from that of the Marxist classics.